The Relationship Between the Level of Husband Support and The Incidence of Baby Blues In Postpartum Mothers At The Practice of Independent Midwives In Jakabaring District, Palembang City - Dea Ananda Aisyah Aisyah; Mitayani Purwoko; Lilis Khairani; Kurniawan (Indonesian Journal of Medical Anthropology, 2026)
Baby blues is an emotional disorder that appears in the first week of postpartum and is characterized by mood swings, anxiety, easy crying, and inability to take care of the baby. One of the factors that affect this condition is the support of the husband as the mother's main companion after childbirth. This study aims to determine the relationship between husband support and the incidence of baby blues in postpartum mothers at the Independent Midwifery Practice, Jakabaring District, Palembang City. The research design used cross-sectional analytical observational with a sample of 75 postpartum mothers who met the inclusion and exclusion criteria. The status of baby blues in respondents showed that severe baby blues was experienced by 26 respondents (34.7%), medium category 29 respondents (38.7%), and mild category 20 respondents (26.7%). Meanwhile, the level of husband support was divided into three categories, namely low support for 22 respondents (29.3%), medium support for 26 respondents (34.7%), and high support for 27 respondents (36.0%). The analysis of the Chi-Square test obtained a p-value = 0.000 so that there was a significant relationship between husband support and the incidence of baby blues.